Pressure-dependent current transport in vertical BP/MoS2 heterostructures - Ofelia Durante; Sebastiano De Stefano; Adolfo Mazzotti; Loredana Viscardi; Filippo Giubileo; Osamah Kharsah; Leon Daniel; Stephan Sleziona; Marika Schleberger; Antonio Di Bartolomeo (Heliyon, 2025)
van der Waals heterostructures between two-dimensional (2D) materials offer versatile platforms for innovative electrical device architectures and applications. Black phosphorus (BP) and molybdenum disulfide (MoS2) emerge as promising candidates for heterostructures, owing to their exceptional electronic properties and gate-tunable capabilities. In this work, we study the electrical properties of a vertical BP/MoS2 heterostructure fabricated onto a SiO2/Si substrate in a back-gate configuration. We focus on the effect of air pressure, from atmospheric pressure to 10−4 mbar, and show that best electrical performances are enabled at the lower pressure. The heterostructure exhibits gate-tunable rectifying current-voltage characteristics, with a rectification ratio close to 103. The rectifying characteristics present a kink in the forward region revealing different conduction mechanisms, namely drift-diffusion and band-to-band tunneling. Furthermore, when used as a transistor, the device shows n-type conduction, high gate modulation with ON/OFF ratio of 106, low off-state current of 10−14A and mobility of 1.6 cm2 V−1 s−1. The results of this work highlight the potential of BP/MoS2 heterostructures for applications in low-power electronics, high-performance transistors, and sensitive pressure sensors.